SIKAP DAN PARTISIPASI PEDAGANG DALAM MEMELIHARA KEBERSIHAN LINGKUNGAN - Lilis Karwati; H Syaefuddin; Lesi Oktiwanti (Jendela PLS: Jurnal Cendekiawan Ilmiah Pendidikan Luar Sekolah, 2017)
Abstract: Attitudes toward cleanliness traders will affect the high participation of traders in waste management so that more and better attitudes towards cleanliness of its environment, public participation in managing the waste, the better. The attitude then form an awareness of environmental hygiene is an important factor in creating a clean environment.The purpose of this study was to determine the relationship between attitudes towards cleanliness with the participation of traders in waste management.The method used in this research is descriptive analytic using a quantitative approach in order to describe and gave a very deep meaning. A population of 229 people and the sample as many as 58 people.The impact of the results obtained by the higher level of awareness trader attitudes towards cleanliness, the higher the participation of traders manage waste in creating a cultural environment clean. Society jointly participate in the management of the process and the results will provoke a far more optimal than the way the applied current. Keywords: Relationships attitude, cleanliness, and participation in waste management